Evaluation of the multifunctional dipeptidyl-peptidase IV and angiotensin converting enzyme inhibitory properties of a casein hydrolysate using cell-free and cell-based assays - Li, Jianqiang; Bollati, Carlotta; Aiello, Gilda; Bartolomei, Martina; Rivardo, Fabrizio; Boschin, Giovanna; Arnoldi, Anna; Lammi, Carmen (Frontiers in Nutrition, 2023)
The objective of this study was the evaluation of the potential pleiotropic effect of a commercially available casein hydrolysate (CH). After an analysis of the composition, the BIOPEP-UWM database suggested that these peptides contained numerous sequences with potential inhibitory activities on angiotensin converting enzyme (ACE) and dipeptidyl-peptidase IV (DPP-IV). The anti-diabetic and anti-hypertensive effects of CH peptides were thus assessed using either cell-free or cell-based assays. More in details, CH displayed inhibitory properties against DPP-IV (IC50 value of 0.38 ± 0.01 mg/mL) and ACE (IC50 value of 0.39 ± 0.01 mg/mL) in the cell-free system. Further, CH reduced the DPP-IV and ACE activities expressed by human intestinal Caco-2 cells by 61.10 ± 1.70% and 76.90 ± 4.47%, respectively, versus untreated cells, at the concentration of 5 mg/mL after 6 h of treatment. This first demonstration of the multifunctional behavior of this material suggests that it may be considered as an anti-diabetic and/or anti-hypertensive ingredient to be included in the formulation of different functional food or nutraceutics.